The humidity in a low-flow dräger fabius anesthesia workstation with or without thermal insulation or a heat and moisture exchanger: A prospective randomized clinical trial - De Oliveira, Sergius A. R. [UNESP]; Lucio, Lorena M. C. [UNESP]; Modolo, Norma S. P. [UNESP]; Hayashi, Yoko [UNESP]; Braz, Mariana Gobbo [UNESP]; Carvalho, Lídia R. [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, José Reinaldo C. [UNESP] (Public Library of Science (PLoS), 2017)
Background During anesthesia, as compared with intensive care, the time of the tracheal intubation is much shorter. An inhaled gas minimum humidity of 20 mgH2 O.L-1 is recommended to reduce the deleterious effects of dry gas on the airways during anesthesia with tracheal intubation. The Fabius GS Premium® anesthesia workstation (Dräger Medical, Lübeck, Germany) has a built-in hotplate to heat gases in the breathing circuit. A heat and moisture exchanger (HME) is used to further heat and humidify the inhaled gas. The humidity of the gases in the breathing circuit is influenced by the ambient temperature. We compared the humidity of the inhaled gases from a low-flow Fabius anesthesia workstation with or without thermal insulation (TI) of the breathing circuit and with or without an HME. Methods We conducted a prospective randomized trial in 41 adult female patients who underwent elective abdominal surgery. The patients were allocated into four groups according to the devices used to ventilate their lungs using a Dräger Fabius anesthesia workstation with a low gas flow (1 L.min-1 ): control, with TI, with an HME or with TI and an HME (TIHME). The mean temperature and humidity of the inhaled gases were measured during 2-h after connecting the patients to the breathing circuit. Results The mean inhaled gas temperature and absolute humidity were higher in the HME (29.2 ±1.3°C; 28.1±2.3 mgH2 O·L-1 ) and TIHME (30.1±1.2°C; 29.4±2.0 mgH2 O·L-1 ) groups compared with the control (27.5±1.0°C; 25.0±1.8 mgH2 OôL-1 ) and TI (27.2±1.1°C; 24.9±1.8 mgH2 O·L-1 ) groups (P = 0.003 and P<0.001, respectively). Conclusions The low-flow Fabius GS Premium breathing circuit provides the minimum humidity level of inhaled gases to avoid damage to the tracheobronchial epithelia during anesthesia. TI of the breathing circuit does not increase the humidity of the inhaled gases, whereas inserting an HME increases the moisture of the inhaled gases closer to physiological values.